Pilot Shortage and Technician Fatigue: Safety Risk Analysis And Policy Implications for Indonesia’s Post-Pandemic Aviation Industry - TU, Wisnu Darjono; Arinta, Farah Khalda; Fachri Muhammad Rasyid (Langit Biru: Jurnal Ilmiah Aviasi, 2026)
In the post-COVID-19 era, Indonesia’s aviation industry faces two major human resource challenges: pilot shortages and technician fatigue. High costs of type rating have left many pilot graduates unemployed despite strong airline demand, while long working hours increase maintenance fatigue risks that threaten flight safety. This study aims to analyse the safety risks arising from pilot shortages and technician fatigue in Indonesia’s post-pandemic aviation industry and to identify relevant policy implications from a human factors perspective. This study applies a qualitative descriptive approach, drawing on secondary data from official reports, academic publications, and aviation regulations, complemented by brief stakeholder interviews. While previous studies generally address pilot shortages and technician fatigue separately, this research integrates both issues within the Indonesian post-pandemic context. The findings reveal strong links between structural barriers, such as high training and certification costs, and operational risks, such as fatigue, which together create a significant aviation safety gap. Policy recommendations include expanding access to type rating programs, enforcing Fatigue Risk Management Systems (FRMS), and strengthening technician certification standards. This integrative analysis contributes a novel perspective to aviation safety literature and offers actionable strategies to support Indonesia’s post-pandemic aviation recovery.